1994
DOI: 10.2169/internalmedicine.33.809
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Vasculitis in a Patient with Dermatomyositis without Muscle Involvement.

Abstract: A 74-year-old female patient with cutaneous ulcerations and typical dermatomyositis (DM) skin rash had no muscle disease for a 1-year and 5 months period. Histological examination of the skin ulceration indicated vascular occlusion without cellular infiltration.Cutaneous ulceration is a very rare manifestation of adult-onset DMpatients without inflammatory myopathy. (Internal Medicine 33: 809-812, 1994)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…This is rarely reported in adults but common in the juvenile form. 2 Feldman et al 3,4 have reported that 9% of 76 patients with adult DM had cutaneous vasculitis. Current evidence suggests that DM may be a humorally mediated disease; hence, it seems to be responsive to drugs that target the B cells like rituximab (antiYCD20 chimeric monoclonal mouse/ human antibody).…”
Section: Discussionmentioning
confidence: 99%
“…This is rarely reported in adults but common in the juvenile form. 2 Feldman et al 3,4 have reported that 9% of 76 patients with adult DM had cutaneous vasculitis. Current evidence suggests that DM may be a humorally mediated disease; hence, it seems to be responsive to drugs that target the B cells like rituximab (antiYCD20 chimeric monoclonal mouse/ human antibody).…”
Section: Discussionmentioning
confidence: 99%
“…Vasculitis over the course of SSc is a rarely observed, mostly as part of the limited scleroderma pattern and is associated with the presence of anti-centromere antibodies [23,24]. Only a few descriptions of cutaneous vasculitis with periungual infarcts and digital ulcerations are reported in the literature in the context of idiopathic inflammatory myopathies [25,26]. In our study, we also noted only a small number of such cases.…”
Section: Discussionmentioning
confidence: 53%